Factors affecting the implementation of the Water Services Provision (WSP) strategy at Amathole District Municipality (ADM) - Snombo, Kanyisa (Rhodes University, Faculty of Commerce, Rhodes Business School, 2017)
Amathole District Municipality (ADM) in the Eastern Cape province of South Africa changed its water service provision strategy in 2012 from decentralized to a centralized strategy as a way of trying to improve its water service delivery. Since this change, no study has been done to explore how the centralized water service strategy has so far been implemented at ADM. The aim of this exploratory qualitative study was to describe how ADM implemented its centralized water strategy and also assess the extent of alignment of strategy execution using Higgins' (2005) 8 "S" model. Purposively, a total of five senior managers were identified and interviewed in East London as they were intimately involved in the daily operation of the water service provision over the years. Data gathered through audio recorded, in-depth and semi-structured interviews with each of the senior managers and also documented reports on Water Service Provision (WSP) were analyzed using thematic analysis into meaningful patterns reflecting each of the components of Higgins' (2005) 8 "S" model. Findings of this qualitative study reveal that senior managers had different but complementary views of what strategy they were implementing at ADM. More importantly, the implementation of centralized water services provision model by ADM was characterized by deep and persistent vacancies of key technical but also managerial positions in the new structure. Furthermore while human and financial resources were inadequate to match with the depth and variety of changes necessary to have the requisite number of staff, ADM implemented the centralized water service strategy with poor skills mix which negatively impacted on quality of water service. While ADM had ten espoused shared values, none of these were commonly and widely shared by employees in their day-to-day world of work. Instead, employee's behavior at ADM was practically shaped by the emergent values of cooperation, and employee care and recognition. Thus there was misalignment between espoused and practiced shared values. Furthermore there was also recurrent and deep misalignment between structure, staff, resources and water quality systems which compounded the difficulties experienced by ADM in pursuit of centralized water service provision. While the use of outsourced mechanical and electrical services was a remedy to staff shortages and the lack of skills mix, it ultimately further aggravated the financial challenges of ADM by draining more of the already limited financial resources. Recommendations for improving the implementation of centralized water service strategy and areas for further research are suggested.
Keywords: Uncatalogued